Options to restrict hematoma expansion after spontaneous intracerebral hemorrhage - Steiner, Thorsten; Bösel, Julian (Stroke, 2010)
Background and Purpose—Secondary expansion of hematoma after spontaneous intracerebral hemorrhage occurs frequently and early with the potential sequelae of functional deterioration or death. The aim of this topical review is to give a summary of current evidence- and experience-based options to avoid or attenuate hematoma expansion. - - Method—We reviewed the literature of the past 10 years on efforts to restrict spontaneous intracerebral hemorrhage expansion by searching Medline and adding related articles known to us. Based on evidence, current guidelines, and our own clinical practice, we have collected consistent and inconsistent pieces of data. These were differentiated according to surgical versus medical approaches, weighed and discussed with regard to expectable benefit, potential risk, and practicability. Finally, we have outlined promising future approaches. - - Results—Although consistent evidence on the topic is generally limited, some important studies have provided data on risk factors predicting spontaneous intracerebral hemorrhage expansion implying ways of directing therapy toward these risk factors. Large trials have shed light on 4 major efforts to avoid hematoma expansion: surgical hematoma treatment, reduction of hypertension, reversal of coagulopathies or anticoagulants, and hemostatic therapy. The results were largely disappointing but provide insights for new trials. Future strategies include the combination of surgical and medical treatment and the use of neuroprotectants. - - Conclusions—Early restriction of intracerebral hemorrhage is of paramount importance because secondary volume expansion leads to outcome deterioration and death. Although there appear to be few indications for neurosurgical measures, nonsurgical measures such as reduction of hypertension and normalization of altered coagulation seem to be beneficial. However, the routine use of coagulation factors outside of warfarin-associated spontaneous intracerebral hemorrhage cannot generally be recommended at present. The same applies for future approaches such as combined medical-surgical approaches and neuroprotective therapies at this point.